World Exhibitions of the Second Half of the 19th Century: A Means of Updating Engineering and Highlighting its Importance - Matos, Ana Cardoso de (2011)
1-World Exhibitions as a means of highlighting the economic, political and technological power of different countries. 2 - The Exhibition as a means of advancing scientific, technical and industrial progress. 3 - Visits of engineers to the World Exhibitions in the 2nd half of the 19thcentury and the transfer of technology. 4- The attempt to define international procedures in the field of engineering: conferences held in association with World Exhibitions.